Aplicação de ultrassom como estratégia para redução de fosfato em emulsões cárneas - Pinton, Mariana Basso (2019)
Phosphates are additives widely used in the manufacture of emulsified meat products. They are mainly responsible for the water holding capacity, giving better gel stability and cooking performance. Ultrasound has been applied for the purpose of modifying the functional properties of proteins, reduction of additives, increase of yield and also improvements in texture. These effects are caused by the phenomenon of cavitation. Meat emulsions with a reduction of 0, 25, 50, 75, and 100% of phosphate levels were produced. Soon after filling, the pieces were sonicated in an ultrasonic bath (normal mode, 60% amplitude, and 25 KHz frequency) for 0, 9, and 18 minutes. The technological, oxidative, and sensory quality was evaluated. The reduction of the phosphate content in the non-sonicated samples led to a decrease in the cooking yield and emulsion stability and impaired the texture profile, and the oxidative and sensory quality of the samples. Although the 9-minute ultrasound treatment was not effective to compensate for defects caused by the phosphate reduction, the application for 18 minutes improved the technological quality and did not increase the lipid oxidation. In addition, it allowed reducing most of the sensory defects caused by the reduction of 50% of the phosphate level.